Struktur Populasi Ternak Sapi Bali di Pulau Semau - Arifandi, Firgilius; Toha, Larry R. W.; Kallau, Novalino H. G.; Winarso, Aji (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Semau Island is an island across the west of the island of Timor which is an area of ​​Kupang Regency with the potential for developing Bali cattle. This study aims to determine the population structure of Bali cattle in Semau Island. This research uses simple random sampling method. Collecting data in the form of primary data (interviews/questionnaires) and secondary data. The total sample used is 110 farmers. The parameters measured in the population structure are livestock birth rates, livestock purchases, livestock mortality, livestock slaughter, livestock sales, livestock income, livestock expenditure, and natural increase values. The results showed that the population structure of Bali cattle on Semau Island which was owned by the respondents was dominated by 455 female cows with a total of 1103 cows. Birth rate of 16.59%, purchase rate of 4.26%, death rate of 4.17%, slaughter rate of 0.18%, sales rate of 10.06%, income rate of 20.85%, expenditure rate of 14.42%, and the Natural Increase (NI) value of 12.42%.